2020
DOI: 10.1002/ccd.28726
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping bicuspid aortic valve stenosis with an hourglass‐shaped balloon for transcatheter aortic valve replacement: A pilot study

Abstract: Objectives We evaluated the safety and usefulness of preparatory anatomical reshaping with a geometric hourglass‐shaped balloon to optimize transcatheter aortic valve replacement (TAVR) outcomes in bicuspid aortic valve (BAV) stenosis. Background TAVR has been increasingly performed for BAV stenosis; however, technical challenges remain. Procedural results are suboptimal given unfavorable valvular anatomies. Methods Eligible patients with BAV stenosis were enrolled to undergo aortic valve predilatation with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(30 reference statements)
0
7
0
1
Order By: Relevance
“…Previous studies have identified several procedural and patient specific variables that may impact the mortality and clinical outcomes in BAV patients undergoing TAVR. These include BAV morphology and degree of calcification, device type/generation, radiological features and surgical approach (14,30,59,(61)(62)(63). Additionally, longterm follow-up data was not included in this study, due to the lack of available studies in the current literature.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Previous studies have identified several procedural and patient specific variables that may impact the mortality and clinical outcomes in BAV patients undergoing TAVR. These include BAV morphology and degree of calcification, device type/generation, radiological features and surgical approach (14,30,59,(61)(62)(63). Additionally, longterm follow-up data was not included in this study, due to the lack of available studies in the current literature.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Because the bicuspid valve often has an elliptical annulus, severe and asymmetric valve calcification, unequal leaflets, a widened ascending aortic internal diameter, and a leaflet opening smaller than the annular internal diameter, these pathological changes are likely to result in a poor TAVI valve implantation position, poor valve stent expansion, and perivalvular residual leakage. To address these issues, some experts have proposed "supra-annular structure assessment", "supra-annular sizing", and "reshaping TAVR" (6,21,22), whose main idea is to select the valve size based on the leaflet structure and recommended valve size in terms of the annular size to prevent poor valve expansion and rupture of the aortic root structure due to oversized prosthetic valves. Based on the aforementioned suggestion, the present study reduced the intraoperative selection of the prosthetic valve size for the bicuspid aortic valve by 1 valve size compared with the measured annular diameter, and the actual intraoperative implantation of the valve will take into account additional factors in selecting the valve size.…”
Section: Discussionmentioning
confidence: 99%
“…In our single center analysis, the TAVR outcome in bicuspid patients was feasible with high device success rate of 84.5% and good performance even with first generation devices. Several recent studies have also suggested the safety and effectiveness of prosthesis undersizing based on supra-annular sizing methods ( 8 , 10 , 38 , 39 ). LIRA method, known as Level of Implantation at the RAphe (LIRA) method, was applicated in 20 raphe-type BAV patients.…”
Section: Discussionmentioning
confidence: 99%